(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Leadership skills are often associated with personal traits, but this paper argues for the critical role of structured education in nurturing potential leaders. Drawing upon global educational practices, the research highlights innovative curriculum designs that prioritize leadership skill-building alongside academic excellence.